การออกแบบและพัฒนาระบบสารสนเทศภูมิศาสตร์ทางโบราณคดีในภาคตะวันออกเฉียงเหนือของประเทศไทย - เกรียงไกร วิทยาอนิวรรตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
To develop web-base Archaeological GIS software for the North-Eastern of Thailand. The software presents the geographic information on Google Maps API, therefore the software contains Google standard map layers consisting of regular map, satellite map and landscape map. To import data, user can specify the location on the map and save it into the system. Project manager may allow access entry to member or general user. The users can zoom the map in and out, hide map layers or part of map layers. The users can analyze geographic information data, for example, by overlaying maps, measures tools, route tools and many query tools.